(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This research, entitled A Billing System for Karen’s Beauty Product, made to create and Implement a Computerize Billing Management System for Karen’s Beauty Product; the goals of pursuing this research are to improve and enhance the daily process of storing Customers’ borrower information and especially Calculation that can consume large digits and handle simultaneously bought items, thus by creating efficiently managing Computation for Karen’s beauty product. The outcome of the system was successful; it was properly implemented while the researchers based the client problem, and all the contents of the system made by the researchers were adapted to the expectation until it was made to become reality; this is helpful in exchange for their manual process despite the creation of the system, the researchers showed the dedication upon creating the system. The researchers implemented a user-friendly application that can provide security in securing important contacts of borrowers and especially Simultaneous Computation that can handle large digits to manage to calculate various bought products. Based on what the provided system can do, the system has big benefits that can positively affect the process and lessen the probability of losing sales and profit.